Vacuum-assisted aspiration biopsy in mammology practice. Analysis of 3-year experience - S. S. Skurikhin; Yu. V. Suvorova (ABV-press, 2020)
Objective: to analyze the 3-year experience of vacuum-assisted aspiration biopsy under ultrasound guidance in patients with focal mammary neoplasms in categories BIRADS 2-5.Materials and methods. The totals of 121 interventions were performed in 121 patients. In 9 (7.4 %) cases there were more than 1 node in the mammary gland.Results. In 97.7 % cases the removed formations were benign. The breast cancer was detected in 5 (2.3 %) cases; there were cases of malignant tumors in each category according to the BIRADS scale. The complications were registered in 15 (12.3 %) cases and did not require surgical treatment. In 77 (63.3 %) cases the results of ultrasound monitoring were obtained in 6 months after the removal of formations, residual tissue was detected in 6 (4.9 %) patients.Conclusions. The vacuum-assisted aspiration biopsy, thus, has a high diagnostic accuracy; the number of completely removed benign formations allows us to consider the method as an alternative to sectoral resection. It is worth saying that a high percentage of complications is associated with the stage of mastering the method; all complications were resolved conservatively.